RETRACTED: ANALISIS GERAK SMASH KEDENG PADA ATLET PUTRA SEPAKTAKRAW CLUB PSTI KABUPATEN DEMAK TAHUN 2021 - Nova Rizky Pratama; Rivan Saghita Pratama (Unnes Journal of Sport Sciences, 2022)
This article has been withdrawn at the request of the Editor-in-Chief. The reason for the withdrawal is because this article was also published in the Journal Of Sport Education (JOPE) and was accepted on 13 January 2022 Link: (https://jope.ejournal.unri.ac.id/index.php/jope/article/view/80103) The requirements for submitting a work for publication are that the creator expressly declares that all of his work is original and has never been published elsewhere. We apologize to readers of the journal that this was not detected during the submission process